Penerapan Asas Itikad Baik Dalam Mediasi Perceraian Perspektif Hukum Islam Dan Hukum Positif - Chusaini Rafsanjani Assadami (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This article discusses the application of the principle of good faith in divorce mediation at the Religious Court of Ambarawa in 2023. The study is motivated by the low success rate of mediation and the need for a more just and humane dispute resolution mechanism within both Islamic and positive law frameworks. Using a qualitative approach and socio-legal method, data were collected through interviews, documentation, and field observations. The findings reveal that although good faith is formally acknowledged, its implementation is often hindered by power imbalances, low legal awareness, and insufficient mediator training. In Islamic law, good faith is rooted in maqāṣid al-sharī‘ah, aiming to preserve justice and reconciliation. In positive law, it functions as a principle to ensure both procedural and substantive justice. This study emphasizes the importance of strengthening mediator competence, increasing public education, and enforcing clearer regulations so that divorce mediation can be conducted meaningfully and fairly.